Double-targeted liposomes coated with matrix metallopeptidase-2-responsive polypeptide nanogel for chemotherapy and enhanced immunotherapy against cervical cancer - Zhimin Bai; Yibo Yang; Zutong Cui; Wenming Liang; Xin Zhang; Zihan Zhang; Jianming Sun; Zhiwei Liu; Kun Li; Ming Shi; Jian Li (Materials Today Bio)
Immunotherapy is a cornerstone in cancer treatment, celebrated for its precision, ability to eliminate residual cancer cells, and potential to avert tumor recurrence. Nonetheless, its effectiveness is frequently undermined by the immunosuppressive milieu created by tumors. This study presents a novel nanogel-based drug delivery system, DOX-4PI@CpG@Lipo@Gel (DPCLG), engineered to respond to Matrix Metallopeptidase-2 (MMP-2)—a protease abundant in the tumor microenvironment (TME). This system enables the controlled release of two distinct types of liposomes within the TME. The first, DOX-4PI@Liposome (DPL), carries doxorubicin (DOX) and 4-phenylimidazole (4PI), targeting cancer cells to provide chemotherapeutic effects while diminishing the immunosuppressive environment. The second, a mannosyl-modified cationic liposome (CL), is loaded with Cytosine phosphate guanine (CpG) oligodeoxynucleotides to specifically target M2 phenotype macrophages, reversing their tumor-associated phenotype (TAM) and activating immune cytokines to promote tumor destruction. Our findings indicate that DPCLG significantly curtails tumor growth, both in vitro and in vivo, mitigates the immunosuppressive TME, and triggers a potent systemic immune response. This study underscores the potential of DPCLG as an advanced, dual-targeting drug delivery system for comprehensive cancer therapy.